Evaluating online bilingual dictionaries: The case of popular free English-Polish dictionaries. Issue 2 (6th February 2017) - Lew, Robert; Szarowska, Agnieszka
Abstract : Language learners today exhibit a strong preference for free online resources. One problem with such resources is that their quality can vary dramatically. Building on related work on monolingual resources for English, we propose an evaluation framework for online bilingual dictionaries, designed to assess lexicographic quality in four major areas: coverage of lexical items, their treatment in the entries, access to lexical information, and presentation of lexicographic data. The proposed framework is applied to a set of six popular bilingual English-Polish dictionaries freely available online, established through an online survey of Polish learners of English.